Two mushroom Leccinum species: similar chemical profiles, different impact in the antioxidant capacity - Reis, Filipa S. (2016)
The chemical profile and the antioxidant activity of two edible mushroom species from the genus Leccinum (Leccinum molle (Bon) Bon and Leccinum vulpinum Watling) were determined. Since few studies exist regarding these mushrooms, the present work contributes to the characterization and valorization of species of the worldwide mycoflora and, in particular, of Portuguese samples. Moreover, this study also shows the importance of the conservation of the mycological resources (known and unknown species), as they could be a source of phytochemicals and bioactive compounds. Actually, mushrooms have been considered over time as valuable foods and advisable to be part of healthy diets [1,2]. The nutritional profile of both species was determined including the analysis of soluble sugars, fatty acids and some vitamins; as also nonnutrients such as polyphenols and organic acids. Since some of the compounds found in both species are referred as having antioxidant activity, this potential was also evaluated. Generally, both species revealed similar nutriente profiles: low fat levels, fructose, mannitol and trehalose as the main soluble sugars, and higher percentages of mono- and polyunsaturated fatty acids (FA) in comparison with saturated FA. Some bioactive compounds were also detected, such as gallic acid, protocatechuic acid and p-hydroxybenzoic acid, as well as organic acids, such as citric and fumaric acids. Although revealing similar chemical profiles, L. vulpinum showed higher antioxidant activity than L. molle in all the tests performed (reducing power, radical scavenging activity and lipid peroxidation inhibition).